Endothelial dysfunction and its treatment in psoriasis patients - Yu. M. Shtoda; N. A. Slesarenko; A. L. Bakulev; S. R. Utz; A. N. Platonova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To assess the effect of a combined cytostatic therapy and sulodexide on the functional condition of the vascular endothelium in psoriatic patients. Materials and methods. The authors examined 74 patients suffering from psoriasis vulgaris and exudative form of psoriasis. Depending on the treatment option, the patients were subdivided into two groups: Group I (n = 41) receiving a cytostatic therapy and Group II where patients received sulodexide as well. The severity of the endothelium dysfunction was assessed based on laboratory assessments such as nitrogen oxide and endothelin 1 in the blood serum. Results. Prior to the treatment, the level of nitrogen oxide was reduced and endothelin 1 was increased in the blood serum of most patients. Substantial improvement of the pathological process was observed in patients from Group I after the cytostatic therapy (total dose of methotrexate: 100 mg); no normalization of laboratory assessments was observed. In patients from Group II receiving methotrexate (total dose: 40 mg) along with sulodexide, improvement or recovery was observed after the completion of the treatment; endothelium dysfunction was normalized. Conclusion. The inclusion of sulodexide in a complex therapy normalizes endothelial dysfunction in case of psoriasis and reduces the dose and duration of methotrexate treatment.